Photosynthetic responses of three citrus species to environmental factors - Machado, Eduardo Caruso; Schmidt, Patrícia Tambelli; Medina, Camilo Lázaro; Ribeiro, Rafael Vasconcelos (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; @font-face font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; p margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Gas exchange responses to irradiance, temperature, air vapor pressure deficit and intercellular CO2 concentration were evaluated in young plants of sweet orange 'Valência', tangor 'Murcote' and acid lime 'Tahiti' plants, under controlled conditions. Maximum rates of CO2 assimilation were around 9.8, 12.8 and 13.0 mmol m-2 s-1, respectively, for 'Valência', 'Murcote' and 'Tahiti', and these differences were related to stomatal conductance and instantaneous carboxylation efficiency. Light saturation of photosynthesis was around 750 mmol m-2 s-1 for 'Valência', whereas 'Murcote' and 'Tahiti' did not show evident light saturation, exhibiting small increases of CO2 assimilation above 1,000 mmol m-2 s-1. The CO2 compensation point was 4.8, 5.8 and 5.4 Pa for 'Valência', 'Murcote' and 'Tahiti', respectively, indicating differences in photorespiration of these citrus species. Leaf temperatures between 25oC and 30oC were optimum for photosynthesis of 'Valência', whereas this optimum was around 30oC for 'Murcote' and 'Tahiti'. At temperatures above or below the optimum range, CO2 assimilation was reduced by partial decrease of stomatal conductance and instantaneous carboxylation efficiency. Reduced CO2 assimilation rate was also caused by increasing vapor pressure deficit from 1.5 to 3.5 kPa, and this effect enhanced when temperature increased from 28oC to 35oC.